Consumer Attitudes towards Mobile Marketing in South Africa - Payne, Colleen (University of the Witswatersrand, Johannesburg, 2020)
Consumer attitudes towards mobile marketing is a relatively new and unexplored phenomenon in South Africa. However, a dearth of research on consumer acceptance towards mobile marketing in South Africa exists. Although studies have been shown in countries such as Turkey, not much has been done in South Africa in relation to consumer attitudes towards mobile marketing. The purpose of this study was to explore how consumer attitudes, such as irritation, credibility and personalisation affect the consumers’ purchase intent on mobile marketing. The demographics of the respondents consisted of more participating females which comprised 53% and 47% males, which indicates that the sample was generally gender balanced. The research philosophy and research design of this study followed a positivism approach which was analysed through a quantitative method using Correlation and Regression Analysis. An on-line questionnaire was sent out on Google Forms to 300 participants, of which 203 participants responded to the survey and the responses collected were exported to Microsoft Excel and then imported into a statistical package, namely IBM SPSS. The research results showed that there is a significant relationship between the variables such as credibility, irritation and personalisation. This relationship leads to a positive decision-making pattern for a consumer’s intention to purchase. Companies need to find more targeted and creative methods to better reach their consumers through mobile marketing efforts as part of their mobile marketing strategy
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in Strategic Marketing (MMSM)
Keywords: Consumer attitud; Mobile marketing; UCTD; Purchase intent; Irritation; Mobile advertising; Mobile sales promotion; SDG-8: Decent work and economic growth